PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS MODEL INKUIRI TERBIMBING UNTUK SISWA KELAS V MI DARUSSALAM MALANG - muafi, Achmad (Ibtidaiyyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research was motivated by the lack of learning media at the MI Darussalam Malang school. This problem results in a decrease in the level of student learning activity and also students' understanding of the material, especially in science subjects. The objectives of this research and development are to (1) develop learning media for Student Worksheets (LKPD) on homogeneous and heterogeneous mixed substance material, (2) assess the feasibility of the product to determine whether there is an increase in understanding of concepts on homogeneous and heterogeneous mixed substance material, and ( 3) find out students' responses regarding the attractiveness of the Student Worksheet (LKPD) learning media. This type of research is Research and Development (R&D). The model in this development is a model using the Analysis, Design, Development, Implementation, Evaluation (ADDIE) model. This research uses the Guided Inquiry development model. The results of the learning media validation were validated by 3 validators with an average percentage of 3.40 for design validation, 3.44, for material validation, and 3.65, for learning validation. 3.49 is the total percentage result for the "fairly valid" category. This learning media is effective to apply to improve students' understanding of the material studied. The results of the student response questionnaire regarding attractiveness showed an average percentage of 80.2% "Positive". ABSTRAK Penelitian ini dilatar belakangi dengan minimnya media pembelajarn di sekolah MI Darussalam Malang. Permasalahan ini berakibat pada menurunnya tingkat keaktifan belajar siswa dan juga pemahaman materi siswa terutama pada mata pembelajaran IPA. Tjuan penelitian dan pengembangan ini yaitu untuk (1) mengembangan media pembelajaran Lembar Kerja Peserta Didik (LKPD) pada materi zat campuran homogen dan heterogen, (2) mengkaji kelayakan produk untuk mengetahui adanya peningkatan pemahaman konsep pada materi zat campuran homogen dan heterogen, dan (3) mengetahui respon siswa mengenai kemenarikan dari media pembelajaran Lembar Kerja Peserta Didik (LKPD). Jenis penelitian ini adalah Research and Development (R&D). Model dalam pengembangan ini adalah model menggunakan model Analisis, Desain, Development, Implementasi, Evaluasi (ADDIE). Penelitian ini menggunakan model pengembangan Inkuiri Terbimbing. Hasil dari validasi media pembelajaran di validasi oleh 3 validator dengan rata-rata presentase sebesar 3,40 untuk validasi desain, 3,44, untuk validasi materi, dan 3,65, untuk validasi pembelajaran. 3,49 merupakan hasil persentase total untuk kategori “cukup valid”. Media pembelajaran ini efektif untuk diterapkan untuk meningkatkan pemahaman materi yang dipelajari peserta didik. Hasil angket respon siswa terhadap kemenarikan menunjukkan rata-rata presentase sebesar 80,2% “Positif”.